PWE-036 Clinical Presentation, Causes and Outcome of Ulcers in Ileo-Cecal Region: A Prospective Study from a Tropical Country. (4th June 2013) - Toshniwal, J; Chawlani, R; Kumar, A; Kumar, M; Arora, A
Abstract : Introduction: Ulcerations in the ileo-cecal (IC) region may have various causes and outcome, depending on the geographical region of the patients. Such data is scarce from tropical countries. Methods: To evaluate the clinical, endoscopic and histologic characteristics of ileocecal ulcers in a tropical country. Prospective study of consecutive patients undergoing colonoscopy, and diagnosed to have ulcerations in the IC region presenting at an tertiary care centre. All patients underwent endoscopic documentation. Biopsy was obtained and their clinical presentation and outcome were recorded. Results: Out of 1632 colonoscopies performed in our hospital from May 2010 to October 2011, 104 patients had ulcerations in the IC region. This population represents the study group. The median age was 44.5 years (range 18–85)and 59% were male. The predominant presentation was lower GI bleed (55.5%), pain abdomen +/-diarrhoea (36.3%), diarrhoea alone (9.9%), or miscellaneous (4.4%). Associated fever was present in 32 (31%) patients. On colonoscopy, terminal ileum could be entered in 96 (92%) cases. The distribution of ulcers was as follows: Ileum alone 40% (38/96), cecum alone 33% (32/96), and both ileum plus cecum 27% (26/96). In the 8 patients in whom ileum could not be entered ulcerations were present in the cecum and the IC valve. The ulcers were multiple in 98% and in 34% there were additional ulcers elsewhere in colon. Based on clinical presentation and investigations, the aetiology of ulcers was classified into infective causes (43%), non-infective causes (29%), and non-specific ulcers (28%) (Table). With infective cause, fever was significantly more common (47% vs 19%; p < 0.01) and cecum was preferentially involved (82% vs 45%; p < 0.01). Three patients (3%) died (all had presented with bleed and had non-specific ulcers), and 8 patients (8%)required surgical treatment. The remaining 93 patients (89%) had an uneventful recovery. Conclusion: Unlike in Western countries the most common (> 40%) cause of ulcerations of the IC region in the tropics is infections. Cecal involvement and fever are important clues to infective cause. These causes must be kept in mind while treating IC ulcers in patients from the tropics. Disclosure of Interest: None Declared.